Sets of covariant residues modulate the activity and thermal stability of GH1 β-glucosidases. - Fábio K Tamaki (Public Library of Science (PLoS), 2014)
The statistical coupling analysis of 768 β-glucosidases from the GH1 family revealed 23 positions in which the amino acid frequencies are coupled. The roles of these covariant positions in terms of the properties of β-glucosidases were investigated by alanine-screening mutagenesis using the fall armyworm Spodoptera frugiperda β-glycosidase (Sfβgly) as a model. The effects of the mutations on the Sfβgly kinetic parameters (kcat/Km) for the hydrolysis of three different p-nitrophenyl β-glycosides and structural comparisons of several β-glucosidases showed that eleven covariant positions (54, 98, 143, 188, 195, 196, 203, 398, 451, 452 and 460 in Sfβgly numbering) form a layer surrounding the active site of the β-glucosidases, which modulates their catalytic activity and substrate specificity via direct contact with the active site residues. Moreover, the influence of the mutations on the transition temperature (Tm) of Sfβgly indicated that nine of the coupled positions (49, 62, 143, 188, 223, 278, 309, 452 and 460 in Sfβgly numbering) are related to thermal stability. In addition to being preferentially occupied by prolines, structural comparisons indicated that these positions are concentrated at loop segments of the β-glucosidases. Therefore, due to these common biochemical and structural properties, these nine covariant positions, even without physical contacts among them, seem to jointly modulate the thermal stability of β-glucosidases.